PENGARUH MINAT DAN MOTIVASI BERWIRAUSAHA TERHADAP JIWA WIRAUSAHA SISWA - Fitri Nurlaili; Sinta Terisnawati (FKIP, Universitas Banten Jaya, 2020)
This research aims to know whether the entrepreneurial interest and entrepreneurship motivation influence entrepreneurial spirit and how much interest and motivation of entrepreneurship influence on entrepreneurial spirit of students. This research conducted during Juni 2019 at SMK Negeri 7 Kota Serang. The population in this research were student of SMK Negeri 7 Kota Serang, sampling using simple random sampling. The data was obtained by distributing questionnaries to 109 respondents. Testing the hypothesis with multiple regression analysis, t-test, f-test, and coefficient of determination. The results of this study indicated that: (1) There was a positive and significant influence of interest in entrepreneurship on entrepreneurial spirit ,this was evidenced by having a regression coefficient t count> t table of (2.781> 1,982) and a significant value of 5%, (2) There was a positive and significant effect of entrepreneurial motivation on entrepreneurial spirit evidenced by having a regression coefficient t count> t table of (4,904> 1,982) and a significant value of 5%, (3) There was a positive and significant influence of interest and motivation in entrepreneurship together on entrepreneurial spirit. This was evidenced by having a regression coefficient fcount> ftabel of (50,478> 3.08) and a significant value of 5%, (4) the coefficient of determination (adjusted R2) obtained at 0.478 or 47.8%, while the rest is 52.2% Entrepreneurial spirit was influenced by variables other variables not examined in this study.